Dynamic effects of COVID-19 vaccination on major acute cardiovascular events and mortality following SARS-CoV-2 infection in a target trial emulation study - Tatjana Meister; Ülo Maiväli; Kaur Tenson; Anna Tisler; Ruth Kalda; Kadri Suija; Anneli Uusküla (Scientific Reports)
Abstract The COVID-19 pandemic presents significant health challenges, including increased risk of mortality and long-term complications. While vaccination has proven remarkably effective in mitigating severe disease and mortality associated with acute COVID-19 infection, the long-term implications of vaccination, particularly its influence on post-COVID cardiovascular events and the temporal dynamics of such effects, remain poorly understood. This target trial emulation study utilizes real-world electronic medical record data from April 2021 to March 2023 to address this gap. We evaluate the effect of pre-infection COVID-19 vaccination on the risk of major acute cardiovascular events (MACE) and all-cause mortality in individuals aged 40–85 years during one year after SARS-CoV-2 infection. Among individuals with COVID-19 (n = 18,223 vaccinated, n = 15,331 not vaccinated), vaccination provided a significant protective effect against MACE (weighted incidence rate ratio [wIRR] 0.71, 95% CI 0.58–0.84) and all-cause mortality (wIRR 0.32, 95% CI 0.28–0.36). This effect persisted for approximately three months after the acute infection. These findings underscore the importance of COVID-19 vaccination in reducing both short-term and long-term health risks associated with the infection.